Improved Power Transformer Winding Fault Detection using FRA Diagnostics – Part 2: Radial Deformation Simulation - Hashemnia, Seyednaser; Abu-Siada, Ahmed; Islam, Syed (Institute of Electrical and Electronics Engineers, 2015)
Frequency response analysis (FRA) is proven to be a powerful tool to detect winding deformation within power transformers. Although the FRA test along with the equipment are well developed, interpretation of FRA signature is still a challenge and it needs skilled personnel to identify and quantify the fault type if exists as at this stage, there is no reliable standard code for FRA signature classification and quantification. As it is very hard to implement faults on physical transformer without damaging it, researchers investigated the impact of various mechanical winding deformations on the transformer FRA signature by randomly changing the value of particular electrical parameters of the transformer equivalent electrical circuit. None of them however, precisely investigated the correlation between physical fault level and the percentage change in each parameter. In this paper, the physical geometrical dimension of a single-phase transformer is simulated using 3D finite element analysis to emulate the real transformer operation. A physical radial deformation of different fault levels is simulated on both low voltage and high voltage windings. The impact of each fault level on the electrical parameters of the equivalent circuit is investigated and the correlation between the fault level and the percentage change in each parameter of the equivalent circuit is provided. This will facilitate precise fault simulation using transformer equivalent electrical circuit and ease the quantification analysis of FRA signature.